Urban Farming: Hydroponic Alternative Solution to Utilize Narrow Land to Increase Food Security in the Islands - Wibawa, Dian Prihardini; Wulandari, Ayu; Saputra, Herry Marta (Universitas Serang Raya, 2025)
The island region, especially in urban areas, has geographical characteristics with limited land that is an obstacle to increasing food security and the community's economy. This condition requires a creative solution, namely the application of urban farming through hydroponic techniques to maximize the use of available resources. This service aims to develop urban agriculture through hydroponics to increase food security and the household economy in Jerambah Gantung Village, Pangkalpinang City. The methods used in this service are socialization, training, and mentoring for the Kenanga Women's Farmers Group (KWT), which consists of 12 women who are expected to be pioneers in the application of urban farming in Pangkapinang City. They are given knowledge and trained in urban farming practices, especially hydroponic techniques. The results of this service are an increase in the knowledge of KWT Kenanga members, as shown by an increase in the average pre-test and post-test results with an initial score of 70 to 95. Then, a skill increase was reflected in the harvest quantity, which increased by 37 percent, or originally 35 kg in the first harvest, to 48 kg in the second harvest. There is also an increase in community involvement and agricultural culture, which is marked by an increase in the implementation of independent hydroponics. Thus, this service not only provides direct benefits for KWT Kenanga members but is also expected to contribute to the development of broader urban farming in Pangkalpinang City.